Polyethylene-Based Compositions, and Films and Articles Including Them - Patent application
Polyethylene-based compositions with tailored densities and additives enhance water vapor barrier and recyclability, addressing the balance of processability and integrity in films.
Patent Information
- Application Number
- JP2021561807
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-02
- Filing Date
- 2020-05-01
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-05-01
AI Technical Summary
Existing polyethylene-based films struggle to balance good processability with improved water vapor barrier performance while maintaining film integrity and recyclability.
Development of polyethylene-based compositions with specific density and melt index ranges, incorporating calcium salt of 1,2-cyclohexanedicarboxylic acid and silica, to enhance water vapor barrier properties while maintaining recyclability.
The compositions provide reduced water vapor transmission rates and improved film barrier performance, allowing for easier recycling and reduced dusting, suitable for use in packaging applications.
Smart Images

Figure 0007601786000001 
Figure 0007601786000002 
Figure 0007601786000003
Abstract
Description
[Technical field]
[0001] The present invention relates to polyethylene-based compositions, films comprising such polyethylene-based compositions, and articles comprising such polyethylene-based compositions.
[0002] Introduction Some packaging, such as food packaging, is designed to protect the contents from the external environment and promote a longer shelf life. Such packaging is often constructed using barrier films with low oxygen transmission rate (OTR) and water vapor transmission rate (WVTR). However, in balancing the barrier properties, the integrity of the packaging is also taken into account, for example, to avoid leakage.
[0003] For many years, the film industry has tried to reduce water vapor transmission rate by various techniques. Some of these are described, for example, in US Patent No. 5,562,905, EP 0 799 274B1, WO01 / 70827, and WO2005 / 090464(A1). Other approaches are described in US Patent No. 6,127,484 and WO2004 / 000933(A1).
[0004] Previous studies in the literature have highlighted the complex relationships between resin morphology, molecular properties, film manufacturing conditions, and the resulting water vapor barrier performance. Summary of the Invention [Problem to be solved by the invention]
[0005] It would be desirable to have new polyethylene resins that can provide improved water vapor barrier performance in addition to having good processability and other properties.
[0006] The present invention provides polyethylene-based compositions suitable for packaging applications, films, and articles. The polyethylene-based compositions, when incorporated into films, provide improved water vapor barrier. In some embodiments, the polyethylene-based compositions, when incorporated into films, provide improved water vapor barrier performance (reduced amount of water vapor passing through the film) while maintaining desired physical properties. By being polyethylene-based, the compositions according to some embodiments of the present invention can be incorporated into multilayer films and articles that are primarily, if not substantially or entirely, composed of polyolefins to provide more easily recyclable films and articles. In some embodiments, the polyethylene-based compositions of the present invention can be incorporated into surface layers of films and exhibit relatively low levels of dusting.
[0007] In one aspect, the polyethylene-based composition suitable for packaging applications comprises: (a) (i) 0.935-0.947 g / cm 3 and a melt index (I2) of less than 0.1 g / 10 minutes; (ii) 63 to 75 weight percent of a second polyethylene fraction; and (b) 90 to 540 ppm of a calcium salt of 1,2-cyclohexanedicarboxylic acid based on the total weight of the polyethylene composition, 13 and a density of at least 0.965 g / cm3. 3 and the melt index (I2) of the polyethylene composition is 0.5 to 10 g / 10 min. In some embodiments, the polyethylene composition has a melt index (I2) of 0.940 to 0.947 g / cm 3 and 25 to 37 weight percent of a first polyethylene fraction having a density in the range of 0.970 g / cm 3and 63 to 75 weight percent of a second polyethylene fraction having a density equal to or greater than 63 to 75 weight percent.
[0008] In another aspect, the invention relates to a film comprising any of the polyethylene-based compositions disclosed herein.
[0009] In another aspect, the invention relates to articles, such as food packaging, comprising any of the polyethylene-based compositions or films disclosed herein.
[0010] These and other embodiments are described in greater detail in the detailed description. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Unless stated to the contrary, implied from the context, or customary in the art, all parts and percentages are by weight, all temperatures are in degrees Celsius, and all test methods are current as of the filing date of this disclosure.
[0012] As used herein, the term "composition" refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0013] "Polymer" means a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term polymer encompasses the term homopolymer, defined below, and the term interpolymer, defined below. Trace amounts of impurities (e.g., catalyst residues) may be incorporated in and / or within the polymer. The polymer may be a single polymer, a polymer blend, or a polymer mixture, including a mixture of polymers formed in situ during polymerization.
[0014] As used herein, the term "homopolymer" refers to a polymer prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure.
[0015] As used herein, the term "interpolymer" refers to polymers prepared by the polymerization of at least two different types of monomers. Thus, the general term interpolymer includes copolymers (used to refer to polymers prepared from two different types of monomers) and polymers prepared from three or more different types of monomers.
[0016] As used herein, the terms "olefin-based polymer" or "polyolefin" refer to a polymer that, in polymerized form, contains a majority amount (based on the weight of the polymer) of an olefin monomer, such as ethylene or propylene, and may optionally contain one or more comonomers.
[0017] As used herein, the term "ethylene / α-olefin interpolymer" refers to an interpolymer that contains, in polymerized form, a majority (>50 mol%) of units derived from ethylene monomer and the remainder being derived from one or more α-olefins. Typical α-olefins used to form ethylene / α-olefin interpolymers are C3-C 10 It is an alkene.
[0018] As used herein, the term "ethylene / α-olefin copolymer" refers to a copolymer that contains, in polymerized form, a majority amount (>50 mol%) of ethylene monomer and an α-olefin as the only two monomers.
[0019] As used herein, the term "α-olefin" refers to an alkene having a double bond in the primary or alpha (α) position.
[0020] "Polyethylene" or "ethylene-based polymer" shall mean a polymer containing units derived from a majority amount (>50 mol%) of ethylene monomer. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), very low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE) which includes both linear and substantially linear low density resins, ethylene-based plastomers (POP) and ethylene-based elastomers (POE), medium density polyethylene (MDPE), and high density polyethylene (HDPE). While these polyethylene materials are generally known in the art, the following explanation may be helpful in understanding the differences among some of these different polyethylene resins.
[0021] The term "LDPE" may also be referred to as "high pressure ethylene polymer", or "highly branched polyethylene", and is defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures in excess of 14,500 psi (100 MPa) using a free radical initiator, such as peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated by reference). LDPE resins typically have a viscosity of 0.916 to 0.935 g / cm. 3 The density is in the range of
[0022] The term "LLDPE" includes both resins made using single-site catalysts, including, but not limited to, traditional Ziegler-Natta catalyst systems and chromium-based catalysts, as well as mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes) and constrained geometry catalysts, phosphinimine and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy), and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers as further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent No. 4,076,698, and / or blends thereof (such as those disclosed in U.S. Patent No. 3,914,342 or U.S. Patent No. 5,854,045). LLDPE can be made by gas phase, liquid phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0023] The term "MDPE" means 0.926 to 0.935 g / cm 3 "MDPE" refers to polyethylene having a density of greater than 2.5, typically produced using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxys), and typically has a molecular weight distribution ("MWD") greater than 2.5.
[0024] The term "HDPE" refers to polyethylene having a viscosity of about 0.935 g / cm, generally prepared using single-site catalysts, including, but not limited to, Ziegler-Natta catalysts, chromium catalysts, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 Over and up to approx. 0.980g / cm 3 It refers to polyethylene having a density of
[0025] The term "ULDPE" refers to poly(ethylene glycol densitometer-type) polymers having a viscosity of 0.855 to 0.912 g / cm, typically prepared using single-site catalysts including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 ULDPE refers to polyethylene having a density of 0.855 to 0.912 g / cm3. ULDPE includes, but is not limited to, polyethylene (ethylene-based) plastomers and polyethylene (ethylene-based) elastomers. Polyethylene (ethylene-based) elastomer plastomers generally have a density of 0.855 to 0.912 g / cm3. 3 has a density of
[0026] "Blend", "polymer blend" and like terms refer to a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art. A blend is not a laminate, although one or more layers of a laminate may contain the blend. Such blends may be formed as dry blends, in situ (e.g., in a reactor), as melt blends, or using other techniques known to those skilled in the art.
[0027] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any ensuing description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically defined or listed.
[0028] The present invention generally relates to polyethylene-based compositions suitable for packaging applications. When incorporated into films, the polyethylene-based compositions can provide reduced water vapor transmission rates. Without wishing to be bound by theory, it is believed that the unique design of the polyethylene composition in combination with a specific amount of nucleating agent can provide improved barrier performance. The polyethylene-based compositions of the present invention can be incorporated into films and articles with improved barrier, particularly increased barrier to water vapor. Because the compositions of the present invention are polyethylene-based, in some embodiments, the films and articles can be formed entirely or substantially entirely from polyolefins, making the films and articles more easily recyclable.
[0029] In one aspect, the polyethylene-based composition suitable for packaging applications comprises: (a) (i) 0.935-0.947 g / cm 3 and a melt index (I2) of less than 0.1 g / 10 minutes; (ii) 63 to 75 weight percent of a second polyethylene fraction; and (b) 90 to 540 ppm of a calcium salt of 1,2-cyclohexanedicarboxylic acid based on the total weight of the polyethylene composition, 13 and a density of at least 0.965 g / cm3. 3 and the melt index (I2) of the polyethylene composition is 0.5 to 10 g / 10 min. In some embodiments, the first polyethylene fraction has a melt index (I2) of 0.940 to 0.947 g / cm 3 In some embodiments, the second polyethylene fraction has a density of 0.970 g / cm 3 In some embodiments, the polyethylene composition has a density of 0.940 to 0.947 g / cm 3and 25 to 37 weight percent of a first polyethylene fraction having a density in the range of 0.970 g / cm 3 and 63 to 75 weight percent of a second polyethylene fraction having a density equal to or greater than 63 to 75 weight percent.
[0030] In some embodiments, the polyethylene composition comprises 30 to 37 weight percent of the first polyethylene fraction.
[0031] In some embodiments, the second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min. In some embodiments, the second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min and up to 10,000 g / 10 min or more. The second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min and up to 10,000 g / 10 min. The second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min and up to 1,000 g / 10 min. In some embodiments, the ratio of the melt index (I2) of the second polyethylene fraction to the melt index (I2) of the first polyethylene fraction is at least 1,000.
[0032] In some embodiments, the polyethylene-based composition has an overall melt index (I2) less than or equal to 2.5 g / 10 min.
[0033] In some embodiments, the polyethylene-based composition has a zero shear viscosity ratio of less than 2.0.
[0034] In some embodiments, the polyethylene composition comprises: 13 The polyethylene composition has less than 0.05 branches per 1,000 carbon atoms as measured using C NMR. In some embodiments, the polyethylene composition comprises: 13The polyethylene composition has less than 0.03 branches per 1,000 carbon atoms as measured using C NMR. In some embodiments, the polyethylene composition has less than 25 non-vinyl unsaturations per million carbons. In some embodiments, the polyethylene composition has less than 20 non-vinyl unsaturations per million carbons. In some embodiments, the polyethylene composition has 13 It has less than 0.05 branches per 1,000 carbon atoms and less than 20 non-vinyl unsaturations per million carbons as measured using C NMR.
[0035] In some embodiments, the polyethylene-based composition further comprises a fatty acid metal salt in an amount of 45 to 360 ppm based on the total weight of the composition. The metal in the fatty acid metal salt is preferably zinc or magnesium. In some embodiments, the fatty acid metal salt is at least one of zinc stearate and zinc palmitate.
[0036] In some embodiments, the polyethylene-based composition further comprises silica in an amount of 75 to 800 ppm, based on the total weight of the composition.
[0037] In some embodiments, when the polyethylene-based composition is incorporated into a monolayer film, the film has a modulus of elasticity (g-mil) / (100 in) or less when measured according to ASTM F1249-06 at 38° C. and 100% relative humidity. 2 - Indicates the WVTR for Japan.
[0038] In another aspect, the invention relates to a film comprising any of the polyethylene-based compositions disclosed herein.
[0039] In another aspect, the invention relates to an article, such as a food package, comprising any of the polyethylene-based compositions or films disclosed herein.
[0040] Polyethylene Composition As described above, the polyethylene composition of the present invention has a viscosity of (i) 0.935 to 0.947 g / cm 3 and a melt index (I2) of less than 0.1 g / 10 minutes; and (ii) from 25 to 37 weight percent of a first polyethylene fraction having a density in the range of 13 and a density of at least 0.965 g / cm3. 3 The melt index (I2) of the polyethylene composition is 0.5 to 10 g / 10 minutes.
[0041] The polyethylene composition may comprise a combination of two or more embodiments as described herein.
[0042] In one embodiment, the polyethylene composition has a viscosity of at least 0.965 g / cm 3 In some embodiments, the polyethylene composition has a density of at least 0.968 g / cm 3 The polyethylene composition, in some embodiments, has a density of up to 0.976 g / cm 3 In some embodiments, the polyethylene composition has a density of 0.965 to 0.976 g / cm 3 , for example, 0.965 to 0.970, or 0.967 to 0.969, or 0.965 to 0.970 g / cm 3 For example, the density may be 0.965 or 0.967 g / cm 3 Lower limit ~ 0.970, 0.972, 0.975, or 0.976 g / cm 3 may be an upper limit of
[0043] The polyethylene composition has a melt index (I2 or I2 at 190° C. / 2.16 kg) of 0.5 to 10 g / 10 min. For example, the melt index (I2 or I2 at 190° C. / 2.16 kg) can be from a lower limit of 0.5, 0.7, 0.9, 1.0, 1.1, 1.2, 1.5, 2, 3, 4, or 5 g / 10 min to an upper limit of 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8, 9, or 10 g / 10 min. In some embodiments, the polyethylene composition has a melt index (I2) of 0.5 to 5 g / 10 min, or 0.5 to 2.5 g / 10 min, or 0.7 to 3 g / 10 min, or 1.0 to 2.0 g / 10 min, or 1.0 to 1.5 g / 10 min.
[0044] In some embodiments, the polyethylene composition has a melt index ratio (I 10 In some embodiments, the polyethylene composition has a melt index ratio (I / I2) of up to 17. 10 In some embodiments, the polyethylene composition has a melt index ratio (I / I2) of 10 to 17. 10 In some embodiments, the polyethylene composition has a melt index ratio (I / I2) of 12 to 17. 10 / I2).
[0045] The polyethylene composition has a low level of branching. In some embodiments, the polyethylene composition comprises: 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms as measured using C NMR. In some embodiments, the polyethylene composition comprises: 13 The polyethylene composition has less than 0.07 branches per 1,000 carbon atoms as measured using C NMR. In some embodiments, the polyethylene composition comprises: 13 In some embodiments, the polyethylene composition has less than 0.05 branches per 1,000 carbon atoms as measured using C NMR. 13 It has less than 0.03 branches per 1,000 carbon atoms as measured using C NMR.
[0046] In some embodiments, the polyethylene composition has a low level of non-vinyl unsaturation. In some embodiments, the polyethylene composition has 1 The polyethylene composition has less than 25 non-vinyl unsaturations per million carbon atoms as measured using H NMR. In some embodiments, the polyethylene composition comprises: 1 It has less than 20 non-vinyl unsaturations per million carbon atoms as determined using H NMR.
[0047] Without wishing to be bound by theory, it is believed that the combination of low levels of branching and low levels of non-vinyl unsaturation in the polyethylene composition provides a higher amount of crystallinity in the polyethylene composition, thereby improving its barrier properties when formed into a film.
[0048] In one embodiment, the polyethylene composition has a ZSVR value of less than 2.0, or from 1.0 to 2.0, or from 1.2 to 1.8, or from 1.3 to 1.7.
[0049] In one embodiment, the polyethylene composition has a ratio of weight average molecular weight to number average molecular weight (M w / M n , measured by conventional GPC), is in the range of 8.0 to 14.0. w / M n ) may range from a lower limit of 8.0, 8.5, 9.0, or 9.5 to an upper limit of 10.0, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, or 14.0. w / M n is 10.0 to 12.0.
[0050] In one embodiment, the polyethylene composition has a number average molecular weight (M nFor example, the number average molecular weight can be from a lower limit of 8,000, 9,000, 10,000, or 11,000 g / mol to an upper limit of 12,000, 13,000, 15,000, or 20,000 g / mol.
[0051] In one embodiment, the polyethylene composition has a weight average molecular weight (M w For example, the weight average molecular weight can be from a lower limit of 100,000, 105,000, or 110,000 g / mol to an upper limit of 115,000, 120,000, or 124,000 g / mol.
[0052] In one embodiment, the polyethylene composition has a z-average molecular weight (M) of at least 350,000 g / mol, such as in the range of 350,000 to 600,000 g / mol. Z For example, the z-average molecular weight can be from a lower limit of 350,000, 375,000, 400,000, 405,000, or 410,000 g / mol to an upper limit of 420,000, 425,000, 450,000, 475,000, 500,000, 550,000, or 600,000 g / mol.
[0053] In one embodiment, the polyethylene composition has an M z / M w In some embodiments, the polyethylene composition has a M ratio of greater than 3.5, each determined by conventional GPC. z / M w ratio (each determined by conventional GPC). z / M w may be 3.0 to 4.0 in some embodiments, or 3.5 to 4.5 in some embodiments, or 3.5 to 4.0 in some embodiments.
[0054] In one embodiment, the polyethylene composition has a ZSVR of less than 2.0 and a M of greater than 3.0. z / M w In another embodiment, the polyethylene composition has a ZSVR of less than 2.0 and a M z / M w ratio (each determined by conventional GPC).
[0055] The polyethylene composition preferably comprises an ethylene-based polymer formed in the absence of a comonomer. In some embodiments, the polyethylene composition comprises at least 99 wt.% of an ethylene-based polymer formed in the absence of a comonomer. In some embodiments, the polyethylene composition comprises at least 99 wt.% of a polymer comprising a majority (>99 mol %) of units derived from ethylene monomer.
[0056] The polyethylene composition used in the polyethylene-based composition of the present invention comprises two fractions of polyethylene.
[0057] The first polyethylene fraction has a viscosity of 0.935 to 0.947 g / cm 3 In some embodiments, the first polyethylene fraction has a density of 0.940 to 0.947 g / cm 3 The first polyethylene fraction has a melt index (I2) of less than 0.1 g / 10 min. In some embodiments, the first polyethylene fraction has a melt index (I2) of 0.01 g / 10 min or greater. In some embodiments, the first polyethylene fraction has a melt index of 0.05 to 0.1 g / 10 min. In some embodiments, the first polyethylene fraction has 13 It has less than 0.10 branches per 1,000 carbon atoms as measured using C NMR.
[0058] In some embodiments, the second polyethylene fraction has a viscosity of 0.970 g / cm 3 End In some embodiments, the first polyethylene fraction has a density of 0.940 to 0.947 g / cm3 and the second polyethylene fraction has a density of 0.970 g / cm 3 In some embodiments, the second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min. In some embodiments, the second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min and up to 10,000 g / 10 min or more. The second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min and up to 10,000 g / 10 min. The second polyethylene fraction has a melt index (I2) of at least 100 g / 10 min and up to 1,000 g / 10 min.
[0059] In some embodiments, the ratio of the melt index (I2) of the second polyethylene fraction to the melt index (I2) of the first polyethylene fraction is at least 1,000.
[0060] The polyethylene composition comprises 25 to 37 weight percent of the first polyethylene fraction and 63 to 75 weight percent of the second polyethylene fraction, based on the total weight of the polyethylene composition. In some embodiments, the polyethylene composition comprises 30 to 37 weight percent of the first polyethylene fraction and 63 to 70 weight percent of the second polyethylene fraction, based on the total weight of the polyethylene composition.
[0061] The polyethylene-based composition comprises at least 97 wt% of the polyethylene composition, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises up to 99 wt% of the polyethylene composition, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 97 wt%-98 wt% of the polyethylene composition, based on the total weight of the polyethylene-based composition.
[0062] The following discussion focuses on the preparation of a first composition for use in embodiments of the present invention.
[0063] polymerization Any conventional polymerization process may be used to produce the polyethylene composition. Such conventional polymerization processes include, but are not limited to, slurry polymerization processes, solution polymerization processes, using one or more conventional reactors, such as loop reactors, isothermal reactors, stirred tank reactors, simultaneous, continuous batch reactors, and / or any combination thereof. The polyethylene composition may be produced, for example, by a liquid phase polymerization process, using one or more loop reactors, adiabatic reactors, and combinations thereof.
[0064] Generally, the solution phase polymerization process is carried out in one or more well-stirred reactors, such as one or more isothermal loop reactors or one or more adiabatic reactors, at a temperature ranging from 115 to 250°C, e.g., 115 to 200°C, and a pressure ranging from 300 to 1,000 psi, e.g., 400 to 750 psi. In some embodiments, the temperature of the first reactor is in the range of 115 to 190°C, e.g., 115 to 175°C, and the temperature of the second reactor is in the range of 150 to 250°C, e.g., 130 to 165°C. In other embodiments, in a single reactor, the reactor temperature is in the range of 115 to 250°C, e.g., 115 to 225°C.
[0065] The residence time in the solution phase polymerization process ranges from 2 to 30 minutes, for example, 10 to 20 minutes. Ethylene, solvent, hydrogen, one or more catalyst systems, optionally one or more cocatalysts, and optionally one or more comonomers are continuously fed to one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents are commercially available under the name ISOPAR E from ExxonMobil Chemical Co. (Houston, Texas). The mixture of polyethylene composition and solvent is then removed from the reactor, and the polyethylene composition is isolated. The solvent is typically recovered via a solvent recovery unit, i.e., a heat exchanger and a gas-liquid separator drum, and then recycled to the polymerization system.
[0066] In one embodiment, the polyethylene composition can be produced by solution polymerization in a dual reactor system, e.g., a dual loop reactor system, where ethylene is polymerized in the presence of one or more catalyst systems. In some embodiments, only ethylene is polymerized. Additionally, one or more cocatalysts may be present. In another embodiment, the polyethylene composition can be produced by solution polymerization in a single reactor system, e.g., a single loop reactor system, where ethylene is polymerized in the presence of two catalyst systems. In some embodiments, only ethylene is polymerized.
[0067] Catalyst system Specific embodiments of the catalyst system that can be used to produce the polyethylene compositions described herein are now described. It is understood that the catalyst system of the present disclosure may be embodied in different forms and should not be construed as being limited to the specific embodiments described in this disclosure. Rather, the embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the subject matter to those skilled in the art.
[0068] The term "independently selected" refers to 1 , R 2 , R 3 , R 4 , and R 5 The R groups, such as R 1 , R 2 , R 3 , R 4 , and R 5 may all be substituted alkyl, or R 1 and R 2 may be substituted alkyl, R 3The terms "aryl" and "aryl" are used herein to indicate the same or similar meanings (e.g., may be aryl, etc.). Use of the singular includes use of the plural and vice versa (e.g., hexane solvent includes hexane). A named R group will generally have a structure recognized in the art as corresponding to the R group having that name. These definitions are intended to supplement and illustrate, not preclude, definitions known to those of skill in the art.
[0069] The term "procatalyst" refers to a compound that has catalytic activity when combined with an activator. The term "activator" refers to a compound that chemically reacts with a procatalyst to convert the procatalyst into a catalytically active catalyst. As used herein, the terms "cocatalyst" and "activator" are interchangeable terms.
[0070] When used to describe certain carbon atom-containing chemical groups, "(C x ~C y A bracketed expression having the form "(C1-C)" means that the unsubstituted form of the chemical group has from x carbon atoms to y carbon atoms, inclusive of x and y. For example, (C1-C 40 ) Alkyl is an alkyl group having 1 to 40 carbon atoms in its unsubstituted form. In some embodiments and general structures, certain chemical groups are R S The parenthetical "(C x ~C y ) for the chemical group R S The substituted version can be represented by any group R S Depending on the identity of R, R may contain more than y carbon atoms. For example, S Exactly one group R is phenyl (-C6H5) S (C1~C 40 "(C)alkyl" can contain from 7 to 46 carbon atoms. Thus, the parenthetical "(C)alkyl" is generally used. x ~C y )" is a group defined as one or more carbon atom-containing substituents R SWhen substituted by, the minimum and maximum total number of carbon atoms in the chemical group shall be the sum of all carbon atom-containing substituents R S The carbon number is determined by adding the total number of carbon atoms from the
[0071] The term "substituted" refers to the replacement of at least one hydrogen atom (-H) bonded to a carbon or heteroatom of a corresponding unsubstituted compound or functional group with a substituent (e.g., R S The term "persubstituted" means that all hydrogen atoms (H) attached to carbon or heteroatoms of the corresponding unsubstituted compound or functional group are replaced by a substituent (e.g., R S The term "polysubstituted" means that at least two, but fewer than all, of the hydrogen atoms bonded to a carbon or heteroatom of the corresponding unsubstituted compound or functional group are replaced by substituents.
[0072] The term "-H" means a hydrogen or hydrogen radical that is covalently bonded to another atom. "Hydrogen" and "-H" are interchangeable and mean the same thing unless otherwise specified.
[0073] "(C1~C 40 The term "(C1-C)hydrocarbyl" means a hydrocarbon radical of 1 to 40 carbon atoms. 40 The term "hydrocarbylene" means a hydrocarbon diradical of 1 to 40 carbon atoms, each of which may be aromatic or non-aromatic, saturated or unsaturated, straight or branched, cyclic (monocyclic and polycyclic, fused and non-fused, polycyclic, including bicyclic, of 3 or more carbon atoms) or acyclic, unsubstituted or substituted with one or more R S has been replaced by
[0074] In the present disclosure, (C1 to C 40 ) Hydrocarbyl is unsubstituted or substituted (C1-C 40 ) Alkyl, (C3-C 40)Cycloalkyl, (C3-C 20 )Cycloalkyl-(C1-C 20 ) Alkylene, (C6-C 40 ) aryl, or (C6-C 20 )Aryl-(C1-C 20 In some embodiments, the above (C1-C 40 Each of the hydrocarbyl groups may contain up to 20 carbon atoms (i.e., (C1-C 20 ) hydrocarbyl), and in other embodiments, up to 12 carbon atoms.
[0075] "(C1~C 40 ) alkyl" and "(C1-C 18 The term "alkyl" means a saturated linear or branched hydrocarbon group of 1 to 40 carbon atoms or 1 to 18 carbon atoms, respectively, the radical being unsubstituted or having one or more R S Substituted by Unsubstituted (C1-C 40 Examples of alkyl are unsubstituted (C1-C 20 ) Alkyl, unsubstituted (C1-C 10 ) alkyl, unsubstituted (C1-C5) alkyl, methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-butyl, 2-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 1-hexyl, 1-heptyl, 1-nonyl, and 1-decyl. 40 Examples of substituted (C1-C 20 ) Alkyl, Substituted (C1-C 10 ) alkyl, trifluoromethyl, and [C 45 ] alkyl. 45 The term "alkyl" (with brackets) means that there are up to 45 carbon atoms in the radical, including the substituents, e.g., one R that is (C1-C5) alkyl, S Replaced by (C 27 ~C 40 )alkyl. Each (C1-C5)alkyl can be methyl, trifluoromethyl, ethyl, 1-propyl, 1-methylethyl, or 1,1-dimethylethyl.
[0076] "(C6~C 40 The term "aryl" refers to an unsubstituted or substituted (one or more R S means a monocyclic, bicyclic, or tricyclic aromatic hydrocarbon radical, of which at least 6 to 14 carbon atoms are aromatic ring carbon atoms, the monocyclic, bicyclic, or tricyclic radical containing one, two, or three rings, respectively, one ring being aromatic and two or three rings being independently fused or non-fused, and at least one of the two or three rings being aromatic. 40 Examples of aryl are unsubstituted (C6-C 20 )Aryl, unsubstituted (C6-C 18 )aryl, 2-(C1-C5)alkyl-phenyl, 2,4-bis(C1-C5)alkyl-phenyl, phenyl, fluorenyl, tetrahydrofluorenyl, indacenyl, hexahydroindacenyl, indenyl, dihydroindenyl, naphthyl, tetrahydronaphthyl, and phenanthrene. 40 Examples of aryl are substituted (C1-C 20 )Aryl, Substituted (C6-C 18 )aryl, 2,4-bis[(C 20 ) alkyl]-phenyl, polyfluorophenyl, pentafluorophenyl, and fluoren-9-on-1-yl.
[0077] "(C3~C 40 The term "cycloalkyl" refers to an unsubstituted or substituted cycloalkyl group that is substituted with one or more R S means a saturated cyclic hydrocarbon radical of 3 to 40 carbon atoms, substituted with other cycloalkyl groups, such as (C x ~C y )Cycloalkyl) has x to y carbon atoms and is unsubstituted or has one or more R S The unsubstituted (C3 to C 40 Examples of cycloalkyl are unsubstituted (C3-C 20 )Cycloalkyl, unsubstituted (C3-C10 ) cycloalkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl. 40 Examples of cycloalkyl are substituted (C3-C 20 )Cycloalkyl, substituted (C3-C 10 ) cycloalkyl, cyclopentanon-2-yl, and 1-fluorocyclohexyl.
[0078] (C1~C 40 Examples of hydrocarbylenes include unsubstituted or substituted (C6-C 40 )Arylene, (C3-C 40 ) cycloalkylene, and (C1-C 40 ) Alkylene (e.g. (C1-C 20 ) alkylene). In some embodiments, the diradicals are on the same carbon atom (e.g., -CH2-), or on adjacent carbon atoms (i.e., 1,2-diradicals), or separated by one, two, or more than two intervening carbon atoms (e.g., 1,3-diradicals, 1,4-diradicals, etc., respectively). Some diradicals include α,ω-diradicals. α,ω-diradicals are diradicals with the greatest carbon backbone spacing between the radical carbons. (C2-C 20 Some examples of alkylene α,ω-diradicals include ethane-1,2-diyl (i.e. -CH2CH2-), propane-1,3-diyl (i.e. -CH2CH2CH2-), 2-methylpropane-1,3-diyl (i.e. -CH2CH(CH3)CH2-). (C6-C 50 ) Some examples of arylene α,ω-diradicals include phenyl-1,4-diyl, naphthalene-2,6-diyl, or naphthalene-3,7-diyl.
[0079] "(C1~C 40 The term "alkylene" refers to an unsubstituted or substituted alkylene with one or more R Smeans a saturated straight or branched diradical having 1 to 40 carbon atoms (i.e., the radical is not a ring atom) substituted with 50 Examples of alkylene are unsubstituted (C1-C 20 ) alkylene, including unsubstituted -CH2CH2-, -(CH2)3-, -(CH2)4-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)8-, -CH2C*HCH3, and -(CH2)4C*(H)CH3, where "C*" represents a carbon atom from which a hydrogen atom has been removed to form a secondary or tertiary alkyl radical. 50 Examples of alkylene are substituted (C1-C 20 ) alkylene, -CF2-, -C(O)-, and -(CH2) 14 C(CH3)2(CH2)5- (i.e., 6,6-dimethyl-substituted normal-1,20-eicosylene). As mentioned above, the two R S Together, (C1~C 18 ) alkylene, so that the substitution (C1-C 50 Examples of alkylenes include 1,2-bis(methylene)cyclopentane, 1,2-bis(methylene)cyclohexane, 2,3-bis(methylene)-7,7-dimethyl-bicyclo[2.2.1]heptane, and 2,3-bis(methylene)bicyclo[2.2.2]octane.
[0080] "(C3~C 40 The term "cycloalkylene" refers to a group that is unsubstituted or has one or more R S "R" means a cyclic diradical (i.e., the radicals are on ring atoms) of 3 to 40 carbon atoms substituted with
[0081] The term "heteroatom" refers to an atom other than hydrogen or carbon. Examples of heteroatoms include O, S, S(O), S(O), Si(R C )2, P(R P ), N(R N ), -N=C(R C )2, -Ge(R C )2-, or -Si(R C)-, and each R C , each R N , and each R P is unsubstituted (C1 to C 18 ) hydrocarbyl or -H. The term "heterohydrocarbon" refers to a molecule or molecular backbone in which one or more carbon atoms are replaced with a heteroatom. 40 The term "heterohydrocarbyl" means a heterohydrocarbon radical of 1 to 40 carbon atoms, and is used interchangeably with "(C1-C 40 The term "heterohydrocarbylene" means a heterohydrocarbon diradical of 1 to 40 carbon atoms, each heterohydrocarbon having one or more heteroatoms. The heterohydrocarbyl radical may be present on a carbon atom or a heteroatom, and the heterohydrocarbyl diradical may be present on (1) one or two carbon atoms, (2) one or two heteroatoms, or (3) a carbon atom and a heteroatom. Each (C1 to C 50 ) heterohydrocarbyl and (C1-C 50 ) Heterohydrocarbylene is unsubstituted or (one or more R S They may be substituted (by) aromatic or non-aromatic, saturated or unsaturated, straight or branched chain, cyclic (including monocyclic and polycyclic, fused polycyclic and non-fused polycyclic) or acyclic.
[0082] (C1~C 40 ) Heterohydrocarbyl is unsubstituted or substituted (C1-C 40 )heteroalkyl, (C1-C 40 ) hydrocarbyl-O-, (C1-C 40 ) Hydrocarbyl-S-, (C1-C 40 ) hydrocarbyl-S(O)-, (C1-C 40 ) hydrocarbyl-S(O)2-, (C1-C 40 ) Hydrocarbyl-Si(R C )2-, (C1~C 40 )hydrocarbyl-N(R N )-, (C1~C 40 ) hydrocarbyl-P(R P )-, (C2~C 40 )heterocycloalkyl, (C2-C19 )Heterocycloalkyl-(C1-C 20 ) alkylene, (C3-C 20 )Cycloalkyl-(C1-C 19 ) Heteroalkylene, (C2-C 19 )Heterocycloalkyl-(C1-C 20 ) Heteroalkylene, (C1-C 40 ) Heteroaryl, (C1-C 19 )Heteroaryl-(C1-C 20 ) Alkylene, (C6-C 20 )Aryl-(C1-C 19 ) heteroalkylene, or (C1-C 19 )Heteroaryl-(C1-C 20 ) heteroalkylene.
[0083] "(C4~C 40 The term "heteroaryl" refers to an unsubstituted or substituted heteroaryl group consisting of a total of 4 to 40 carbon atoms and 1 to 10 heteroatoms (one or more R S (C) means a monocyclic, bicyclic, or tricyclic heteroaromatic hydrocarbon radical, the monocyclic, bicyclic, or tricyclic radical containing 1, 2, or 3 rings, respectively, the 2 or 3 rings being independently fused or non-fused, and at least one of the 2 or 3 rings being heteroaromatic. Other heteroaryl groups, such as, for example, generally (C x ~C y ) Heteroaryl, (C4-C 12 ) heteroaryl, etc., has x to y carbon atoms (e.g., 4 to 12 carbon atoms) and is unsubstituted or substituted with one or more R SThe monocyclic heteroaromatic hydrocarbon radical is a 5-membered or 6-membered ring. The 5-membered ring has 5 minus h carbon atoms, where h is the number of heteroatoms and can be 1, 2, or 3, and each heteroatom can be O, S, N, or P. Examples of 5-membered heteroaromatic hydrocarbon radicals include pyrrol-1-yl, pyrrol-2-yl, furan-3-yl, thiophen-2-yl, pyrazol-1-yl, isoxazol-2-yl, isothiazol-5-yl, imidazol-2-yl, oxazol-4-yl, thiazol-2-yl, 1,2,4-triazol-1-yl, 1,3,4-oxadiazol-2-yl, 1,3,4-thiadiazol-2-yl, tetrazol-1-yl, tetrazol-2-yl, and tetrazol-5-yl. The six-membered ring has 6 minus h carbon atoms, where h is the number of heteroatoms, which can be 1 or 2, and the heteroatoms can be N or P. Examples of six-membered heteroaromatic hydrocarbon radicals are pyridin-2-yl, pyrimidin-2-yl, and pyrazin-2-yl. The bicyclic heteroaromatic hydrocarbon radicals can be fused 5,6- or 6,6-ring systems. Examples of fused 5,6-ring bicyclic heteroaromatic hydrocarbon radicals include indol-1-yl and benzimidazol-1-yl. Examples of fused 6,6-ring bicyclic heteroaromatic hydrocarbon radicals include quinolin-2-yl and isoquinolin-1-yl. The tricyclic heteroaromatic hydrocarbon radicals can be fused 5,6,5-, 5,6,6-, 6,5,6-, or 6,6,6-ring systems. An example of a fused 5,6,5-ring system is 1,7-dihydropyrrolo[3,2-f]indol-1-yl. An example of a fused 5,6,6-ring system is 1H-benzo[f]indol-1-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,6,6-ring system is acridine-9-yl.
[0084] The heteroalkyl group is any of (C1-C 50) or fewer carbon atoms and one or more heteroatoms. Similarly, heteroalkylene may be a saturated straight or branched chain diradical containing 1 to 50 carbon atoms and one or more heteroatoms. Heteroatoms as defined above include, but are not limited to, Si(R C )3, Ge(R C )3, Si(R C )2, Ge(R C )2, P(R P )2, P(R P ), N(R N )2, N(R N ), N, O, OR C , S, S.R. C , S(O), and S(O), each of the heteroalkyl and heteroalkylene groups may be unsubstituted or may contain one or more R S is replaced by
[0085] Unsubstituted (C2~C 40 Examples of heterocycloalkyl include unsubstituted (C-C 20 )Heterocycloalkyl, unsubstituted (C2-C 10 ) heterocycloalkyl, aziridin-1-yl, oxetan-2-yl, tetrahydrofuran-3-yl, pyrrolidin-1-yl, tetrahydrothiophene-S,S-dioxid-2-yl, morpholin-4-yl, 1,4-dioxan-2-yl, hexahydroazepin-4-yl, 3-oxa-cyclooctyl, 5-thio-cyclononyl, and 2-aza-cyclodecyl.
[0086] The term "halogen atom" or "halogen" refers to a radical of a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), or an iodine atom (I). The term "halide" refers to a radical of a fluoride atom (F - ), chloride (Cl - ), bromide (Br - ), or iodide (I - ) means the anionic form of a halogen atom.
[0087] The term "saturated" means lacking carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen double bonds, carbon-phosphorus double bonds, and carbon-silicon double bonds. A saturated chemical group is one or more substituents R S When substituted with, one or more double and / or triple bonds may be optionally substituted with a substituent R S The term "unsaturated" refers to the inclusion of one or more carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds; when present, the substituent R S It is meant to exclude any such double bonds which may be present in or, if present, in a (hetero)aromatic ring.
[0088] According to some embodiments, the catalyst system for producing the polyethylene composition comprises a metal-ligand complex according to formula (I). [ka]
[0089] In formula (I), M is a metal selected from titanium, zirconium, or hafnium, the metal is in a formal oxidation state of +2, +3, or +4, n is 0, 1, or 2, when n is 1, X is a monodentate or bidentate ligand, and when n is 2, each X is a monodentate ligand and is the same or different, the metal-ligand complex is globally neutrally charged, and each Z is independently selected from -O-, -S-, -N(R N )-, or -P(R P )-, and L is selected from (C1 to C 40 ) hydrocarbylene or (C1-C 40 ) heterohydrocarbylene, (C1-C 40 ) the hydrocarbylene has a moiety that includes a linker skeleton of 1 to 10 carbon atoms (to which L is attached) that connects the two Z groups of formula (I), or (C1 to C 40) heterohydrocarbylene has a moiety that includes a linker skeleton of 1 to 10 atoms that connects the two Z groups of formula (I), (C1-C 40 Each of the 1 to 10 atoms of the 1 to 10 atom linker backbone of the heterohydrocarbylene is independently a carbon atom or a heteroatom, and each heteroatom is independently O, S, S(O), S(O), Si(R C )2, Ge(R C )2, P(R C ), or N(R C ) and each R C However, independently (C1~C 30 ) hydrocarbyl or (C1-C 30 ) heterohydrocarbyl, R 1 and R 8 However, independently, -H, (C1~C 40 ) hydrocarbyl, (C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) 2NC(O)-, halogen, and a radical having formula (II), formula (III), or formula (IV). [ka] In formulas (II), (III), and (IV), R 31~35 , R 41~48 , or R 51~59 Each of the following is independently (C1 to C 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(RC )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N )2NC(O)-, halogen, or -H, provided that R 1 or R 8 is a radical having formula (II), formula (III), or formula (IV).
[0090] In formula (I), R 2~4 , R 5~7 , and R 9~16 Each of the following is independently (C1 to C 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R C ) 2NC(O)-, halogen, and -H.
[0091] In some embodiments, the polyethylene composition is formed using a first catalyst according to formula (I) in a first reactor and a different catalyst according to formula (I) in a second reactor.
[0092] In one exemplary embodiment in which a dual loop reactor is used, the procatalyst used in the first loop is zirconium, [[2,2′′-[[bis[1-methylethyl)germylene]bis(methyleneoxy-κO)]bis[3′,5,5″-tris(1,1-dimethylethyl)-5′-octyl[1,1′:3′,1″-terphenyl]-2′-olato-κO]](2-)]dimethyl-, having the chemical formula C 86 H 128 F2GeO4Zr and has the following structure: [ka] In such an embodiment, the procatalyst used in the second loop is zirconium, [[2,2'''-[1,3-propanediylbis(oxy-κO)[bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5'-(dimethyloctylsilyl)-3'-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-olato-κO]](2-)]dimethyl, having the chemical formula C 107 H 154 N2O4Si2Zr and has the following structure: [ka]
[0093] Cocatalyst Component The catalyst system comprising the metal-ligand complex of formula (I) can be made catalytically active by any technique known in the art for activating metal-based catalysts for olefin polymerization reactions. For example, the system comprising the metal-ligand complex of formula (I) can be made catalytically active by contacting the complex with an activating cocatalyst or combining the complex with an activating cocatalyst. Suitable activating cocatalysts for use herein include alkylaluminum, polymeric or oligomeric alumoxanes (also known as aluminoxanes), neutral Lewis acids, and non-polymeric, non-coordinating, ion-forming compounds, including the use of such compounds under oxidizing conditions. A suitable activation technique is bulk electrolysis. Combinations of one or more of the foregoing activating cocatalysts and techniques are also contemplated. The term "alkylaluminum" refers to monoalkylaluminum dihydrides or dihalides, dialkylaluminum hydrides or halides, or trialkylaluminum. Examples of polymeric or oligomeric alumoxanes include methylalumoxane, triisobutylaluminum modified methylalumoxane, and isobutylalumoxane.
[0094] The Lewis acid activator (cocatalyst) may be any of the Lewis acid activators described herein, which may be any of the Lewis acid activators having one to three (C1-C 20 In one embodiment, the Group 13 metal compound includes a tri((C1-C) hydrocarbyl substituent. 20 )hydrocarbyl)substituted aluminum or tri((C1-C 20 In another embodiment, the Group 13 metal compound is a tri(hydrocarbyl)-substituted aluminum, tri((C1-C 20 )hydrocarbyl)-boron compounds, tri((C1-C 10 ) alkyl) aluminum, tri((C6-C 18)aryl)boron compounds and their halogenated (including perhalogenated) derivatives. In further embodiments, the Group 13 metal compound is tris(fluoro-substituted phenyl)borane, tris(pentafluorophenyl)borane. In some embodiments, the activating cocatalyst is tris((C1-C 20 ) hydrocarbyl borates (e.g., trityl tetrafluoroborate) or tri((C 20 )hydrocarbyl)ammonium tetra((C1-C 20 )hydrocarbyl)boranes (e.g., bis(octadecyl)methylammonium tetrakis(pentafluorophenyl)borane). As used herein, the term "ammonium" refers to any of the ((C1-C 20 )Hydrocarbyl)4N + , ((C1~C 20 )hydrocarbyl)3N(H) + , ((C1~C 20 )hydrocarbyl)2N(H)2 + , (C1~C 20 ) HydrocarbylN(H)3 + , or N(H)4 + Each of the nitrogen cations (C1 to C 20 ) Hydrocarbyls, when present in two or more occurrences, may be the same or different.
[0095] As a combination of neutral Lewis acid activators (cocatalysts), tri((C1-C4) alkyl)aluminum and tri((C6-C 18)aryl)boron compounds, especially tris(pentafluorophenyl)borane. Other embodiments are combinations of such neutral Lewis acid mixtures with polymeric or oligomeric alumoxanes, and combinations of a single neutral Lewis acid, especially tris(pentafluorophenyl)borane, with polymeric or oligomeric alumoxanes. The ratio of the number of moles of (metal-ligand complex):(tris(pentafluorophenylborane):(alumoxane) [e.g., (Group 4 metal-ligand complex):(tris(pentafluorophenylborane):(alumoxane)] is 1:1:1 to 1:10:30, and in other embodiments is 1:1:1.5 to 1:5:10.
[0096] A catalyst system comprising the metal-ligand complex of formula (I) can be activated to form an active catalyst composition by combining one or more cocatalysts, such as cation-forming cocatalysts, strong Lewis acids, or combinations thereof. Suitable activating cocatalysts include polymeric or oligomeric aluminoxanes, particularly methylaluminoxane, as well as inert, compatible, non-coordinating, ion-forming compounds. Exemplary suitable cocatalysts include modified methylaluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyl, tetrakis(pentafluorophenyl)borate (1 - ) amines, and combinations thereof.
[0097] In some embodiments, one or more of the aforementioned activating cocatalysts are used in combination with each other. Particularly preferred combinations are mixtures of tri((C1-C4)hydrocarbyl)aluminum, tri((C1-C4)hydrocarbyl)borane, or ammonium borate with oligomeric or polymeric alumoxane compounds. The ratio of the total number of moles of the one or more metal-ligand complexes of formula (I) to the total number of moles of the one or more activating cocatalysts is 1:10,000 to 100:1. In some embodiments, this ratio is at least 1:5000, in some other embodiments at least 1:1000, and not more than 10:1, and in some other embodiments not more than 1:1. When alumoxane is used alone as the activating cocatalyst, it is preferred that the number of moles of alumoxane used is at least 100 times the number of moles of the metal-ligand complexes of formula (I). When tris(pentafluorophenyl)borane is used alone as the activating cocatalyst, in some other embodiments, the number of moles of tris(pentafluorophenyl)borane used relative to the total number of moles of one or more metal-ligand complexes of formula (I) is 0.5:1 to 10:1, 1:1 to 6:1, or 1:1 to 5:1. The remaining activating cocatalysts are generally used in molar amounts approximately equal to the total molar amount of one or more metal-ligand complexes of formula (I).
[0098] Calcium salt of 1,2-cyclohexanedicarboxylic acid The polyethylene-based composition of the present invention further comprises a calcium salt of 1,2-cyclohexanedicarboxylic acid, which is a type of nucleating agent that has been found to significantly improve the moisture barrier (i.e., reduce the amount of moisture that permeates the film) of films formed from the polyethylene-based composition when used in appropriate amounts in combination with the polyethylene compositions described herein.
[0099] The amount of calcium salt of 1,2-cyclohexanedicarboxylic acid used in the polyethylene-based composition is important in providing the desired moisture barrier performance (i.e., reduction in the amount of moisture that permeates the film). The polyethylene-based composition comprises 90 to 540 ppm of calcium salt of 1,2-cyclohexanedicarboxylic acid, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 150 to 525 ppm of calcium salt of 1,2-cyclohexanedicarboxylic acid, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 165 to 495 ppm of calcium salt of 1,2-cyclohexanedicarboxylic acid, based on the total weight of the polyethylene-based composition.
[0100] In some embodiments, the calcium salt of 1,2-cyclohexanedicarboxylic acid may be provided with a fatty acid metal salt, such as zinc stearate, zinc palmitate, and mixtures thereof. Based on how the zinc stearate is commercially prepared, some zinc palmitate may also be present, as commercially available stearic acid often contains significant amounts of palmitic acid. In some such embodiments, the polyethylene-based composition comprises 45-360 ppm of at least one of zinc stearate and zinc palmitate, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 50-275 ppm of zinc stearate and / or zinc palmitate, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 85-255 ppm of zinc stearate and / or zinc palmitate, based on the total weight of the polyethylene-based composition.
[0101] One non-limiting example of a calcium salt of 1,2-cyclohexanedicarboxylic acid that can be used in embodiments of the present invention is Hyperform HPN-20E from Milliken Chemical of Spartanburg, South Carolina. Hyperform HPN-20E comprises 60-70 weight percent of the calcium salt of 1,2-cyclohexanedicarboxylic acid and 30-40 weight percent of zinc stearate / palmitate. In some embodiments, the polyethylene-based composition comprises 150-800 ppm of Hyperform HPN-20E, based on the total weight of the polyethylene-based composition. The polyethylene-based composition comprises, in some embodiments, 250-750 ppm of Hyperform HPN-20E, based on the total weight of the polyethylene-based composition.
[0102] In some embodiments, the calcium salt of 1,2-cyclohexanedicarboxylic acid (and fatty acid metal salts, e.g., zinc stearate and / or zinc palmitate, if also included) can be provided as a masterbatch by blending it with a carrier resin prior to combining with the polyethylene composition described herein. In some such embodiments, the carrier resin is a polyethylene having a melt index (I2) of 4 to 12 g / 10 min. In some embodiments in which the calcium salt of 1,2-cyclohexanedicarboxylic acid and zinc stearate / zinc palmitate are provided as a masterbatch, the masterbatch comprises 2 to 4 weight percent of the calcium salt of 1,2-cyclohexanedicarboxylic acid and zinc stearate / zinc palmitate, based on the total weight of the masterbatch. In one embodiment, the carrier resin is a narrow molecular weight distribution high density polyethylene homopolymer having a density of 0.965 and a melt index (I2) of 8 to 9 g / 10 min. In some embodiments, the masterbatch can also include other additives. Depending on the total amount of additives included, the masterbatch can comprise 85 to 98 weight percent of the carrier resin, based on the total weight of the masterbatch.
[0103] silica In some embodiments, the polyethylene composition further comprises silica, which, when used in appropriate amounts in combination with the polyethylene compositions described herein, has been found to reduce the level of dusting in films formed from the polyethylene compositions.
[0104] The amount of silica used in the polyethylene-based composition can be important to reduce the level of dusting when the polyethylene-based composition is incorporated into a surface layer of a film. In some embodiments, the polyethylene-based composition comprises 75 to 800 ppm of silica, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 100 to 500 ppm of silica, based on the total weight of the polyethylene-based composition.
[0105] One non-limiting example of a silica that can be used in embodiments of the present invention is Sylobloc 45, available from Grace Davison Company.
[0106] In some embodiments, talc can be used in addition to or as a replacement for silica.
[0107] In some embodiments, the silica can be provided as a masterbatch by blending it with the carrier resin, the calcium salt of 1,2-cyclohexanedicarboxylic acid, and the zinc stearate / palmitate prior to combining with the polyethylene composition described herein. The masterbatch can be as described above in relation to the calcium salt of 1,2-cyclohexanedicarboxylic acid and the zinc stearate / palmitate. The amount of silica in the masterbatch can be based on the target silica for the overall polyethylene-based composition.
[0108] film In some embodiments, the invention relates to a film formed from any of the inventive polyethylene-based compositions as described herein.
[0109] The polyethylene-based composition, when incorporated into a film, provides an improved water vapor barrier. In some embodiments, when the polyethylene-based composition is incorporated into a monolayer film, the film has a water vapor barrier of 0.15 or less (g-mil) / (100 in) measured according to ASTM F1249-06 at 38° C. and 100% relative humidity. 2 In some embodiments, when the polyethylene-based composition is incorporated into a monolayer film, the film exhibits a WVTR of 0.10 or less (g-mils) / (100 in.·days) when measured according to ASTM F1249-06 at 38° C. and 100% relative humidity. 2 - Indicates the WVTR for Japan.
[0110] In some embodiments, when incorporated into a surface layer of a monolayer or multilayer film, the film can exhibit a desirable (i.e., low) level of dusting. Low levels of dusting are advantageous during the manufacture of the film and when converting the film into other articles. If the surface layer has printing, low dusting also aids in better print retention on the article.
[0111] In some embodiments of the multilayer film of the present invention, the multilayer film may include the polyethylene-based composition of the present invention in a surface layer and also in an inner layer. In some such embodiments, by using the same polyethylene-based composition in the surface layer and in the inner layer, the multilayer film may be significantly simplified in terms of the number of different polymers incorporated therein.
[0112] In some embodiments, the film is a blown film. In some embodiments, the film is a monolayer film. In some embodiments, the film is a multilayer film. Films can be formed from the polyethylene-based compositions of the present invention using methods and equipment known to those skilled in the art.
[0113] The amount of polyethylene-based composition used in the films of the present invention can depend on several factors including, for example, whether the film is a monolayer or multilayer film, the other layers of the film if it is a multilayer film, the desired barrier properties of the film, the end use of the film, etc. In some embodiments where the film is a multilayer film, the polyethylene-based composition of the present invention can be provided in a monolayer to provide barrier properties.
[0114] The films of the present invention can have a variety of thicknesses. The thickness of the blown film can depend on several factors, including, for example, whether the film is a monolayer or multilayer film, the other layers of the film if it is a multilayer film, the desired properties of the film, the end use of the film, and others. In some embodiments, the films of the present invention have a thickness of up to 10 mils. For example, the blown film can have a thickness of 0.25 mils, 0.5 mils, 0.7 mils, 1.0 mils, 1.75 mils, or 2.0 mils at lower limits to 4.0 mils, 6.0 mils, 8.0 mils, or 10 mils at upper limits.
[0115] In embodiments where the film comprises a multilayer film, the number of layers of the film can depend on several factors including, for example, the desired properties of the film, the desired thickness of the film, the content of other layers in the film, the end use of the film, the equipment available to manufacture the film, etc. Multilayer blown films can include up to 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11 layers in various embodiments.
[0116] The polyethylene-based composition of the present invention can be used in two or more layers of the film in some embodiments. Other layers in the multilayer film of the present invention can include, in various embodiments, a polymer selected from the composition of the present invention, LLDPE, VLDPE (very low density polyethylene), MDPE, LDPE, HDPE, HMWHDPE (high molecular weight HDPE), propylene-based polymers, polyolefin plastomers (POP), polyolefin elastomers (POE), olefin block copolymers (OBC), ethylene vinyl acetate, ethylene acrylic acid, ethylene methacrylic acid, ethylene methyl acrylate, ethylene ethyl acrylate, ethylene butyl acrylate, isobutylene, maleic anhydride grafted polyolefins, ionomers of any of the foregoing, or combinations thereof. In some embodiments, the multilayer film of the present invention can include one or more tie layers known to those skilled in the art.
[0117] It should be understood that any of the foregoing layers may further include one or more additives known to those skilled in the art, such as, for example, antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblocking agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and blowing agents. In some embodiments, the polyethylene-based composition includes up to 3 weight percent of such additional additives. All individual values and subranges from 0 to 3 weight percent are included and disclosed herein, for example, the total amount of additives in the polymer blend may be from a lower limit of 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, or 4.5 weight percent to an upper limit of 1, 2, 3, 4, or 5 weight percent.
[0118] Being polyethylene-based, the polyethylene-based compositions of the present invention can be incorporated into multilayer films and articles that are primarily, if not substantially or entirely, composed of polyolefins to provide more easily recyclable films and articles, according to some embodiments of the present invention. The polyethylene-based compositions of the present invention are particularly advantageous for providing films in which the film is formed primarily of polyolefins, such as polyethylene and / or polypropylene. For example, coated films in which the film is primarily comprised of polyethylene or polypropylene have improved recyclability profiles, in addition to other advantages that the use of such polymers may provide. In some embodiments, the film comprises 95 weight percent or more of polyethylene, based on the total weight of the film. In other embodiments, the film comprises 96 weight percent or more, 97 weight percent or more, 98 weight percent or more, or 99 weight percent or more of polyethylene, based on the total weight of the film.
[0119] In some embodiments, a film including a layer formed from the inventive polyethylene-based composition can be laminated to another film.
[0120] Films of the present invention, in some embodiments, can be corona treated and / or printed (eg, reverse printed or front printed) using techniques known to those of ordinary skill in the art.
[0121] In some embodiments, the films of the present invention can be uniaxially (eg, machine direction) or biaxially oriented using techniques known to those skilled in the art.
[0122] Goods Embodiments of the invention also relate to articles, such as packaging, formed from or incorporating the inventive polyethylene-based compositions (or films incorporating the inventive polyethylene-based compositions). Such packaging can be formed from any of the inventive polyethylene-based compositions (or films incorporating the inventive polyethylene-based compositions). The inventive polyethylene-based compositions are particularly useful in articles where a high moisture vapor barrier is desired.
[0123] Examples of such articles include flexible packaging, pouches, stand-up pouches, and pre-made packages or pouches. In some embodiments, the multilayer films or laminates of the present invention can be used in food packaging. Examples of food products that can be included in such packaging include meat, cheese, cereal, nuts, juice, sauce, and the like. Such packaging can be formed using techniques known to those skilled in the art based on the teachings herein and based on the particular application of the packaging (e.g., type of food, amount of food, etc.).
[0124] Test Method Unless otherwise indicated herein, the following analytical methods are used in describing aspects of the present invention. Melt Index Melt index I2 (or I2) and I 10 (or I10) were measured according to ASTM D-1238 (Method B) at 190° C. and loads of 2.16 kg and 10 kg, respectively. The values are reported in g / 10 min.
[0125] density Samples for density measurements were prepared according to ASTM D4703. Measurements were performed according to ASTM D792, Method B within 1 hour of sample pressing.
[0126] Water Vapor Transmission Rate The WVTR of a film is measured at 38° C., 100% relative humidity, and approximately 50 microns thick using a Mocon W3 / 33 according to ASTM F1249-06.
[0127] Conventional Gel Permeation Chromatography (Conventional GPC) The GPC-IR high temperature chromatography system from PolymerChar (Valencia, Spain) is equipped with a two-angle laser light scattering detector model 2040 from Precision Detectors (Amherst, MA), an IR5 infrared detector and a four-capillary viscometer, both from PolymerChar. Data collection was performed using PolymerChar Instrument Control software and data collection interface. The system is equipped with an online solvent degassing device and pumping system from Agilent Technologies (Santa Clara, CA).
[0128] The injection temperature is controlled at 150 degrees Celsius. The columns used are three 10 micron "Mixed-B" columns from Polymer Laboratories (Shropshire, UK). The solvent used is 1,2,4-trichlorobenzene. The samples are prepared at a concentration of "0.1 grams of polymer in 50 milliliters of solvent". The chromatography solvent and the sample preparation solvent each contained "200 ppm of butylated hydroxytoluene (BHT)". Both solvent sources are nitrogen sparged. The ethylene-based polymer samples are gently stirred at 160 degrees Celsius for 3 hours. The injection volume is "200 microliters" and the flow rate is "1 milliliter / minute". The GPC column set is calibrated by running 21 "narrow molecular weight distribution" polystyrene standards. The molecular weights ("MW") of the standards range from 580 to 8,400,000 g / mol, and the standards are contained in six "cocktail" mixtures. Each standard mixture has at least 10 between individual molecular weights. Standard mixtures are purchased from Polymer Laboratories. Polystyrene standards are prepared at 0.025 g in 50 mL of solvent for molecular weights of 1,000,000 g / mol and above, and 0.050 g in 50 mL of solvent for molecular weights less than 1,000,000 g / mol.
[0129] The polystyrene standards are dissolved at 80° C. with gentle stirring for 30 minutes. The narrow standards mixtures are run in order of decreasing highest molecular weight component first to minimize degradation. The polystyrene standard peak molecular weights were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Letters, 6, 621 (1968)). Mpolyethylene=A×(Mpolystyrene) B Convert to polyethylene molecular weight using (Equation 1): where M is the molecular weight, A is equal to 0.4316, and B is equal to 1.0.
[0130] Calculate the number average molecular weight (Mn-conventional GPC), weight average molecular weight (Mw-conventional GPC), and z-average molecular weight (Mz-conventional GPC) according to the following Equations 2-4.
[0131]
number
[0132] In Equations 2-4, RV is the column retention volume (linearly spaced) collected at "1 point per second", IR is the baseline subtracted IR detector signal in volts from the IR5 measurement channel of the GPC instrument, and M PE is the polyethylene equivalent MW determined from Equation 1. Data calculations are performed using PolymerChar's "GPC One software (version 2.013H)."
[0133] Creep Zero Shear Viscosity Measurement Method Zero shear viscosity is obtained by creep testing on an AR G2 stress-controlled rheometer (TA Instruments, New Castle, Del.) using "25 mm diameter" parallel plates at 190°C. The rheometer oven is set to the test temperature for at least 30 minutes before zeroing the fixture. At the test temperature, a compression molded sample disk is inserted between the plates and allowed to equilibrate for 5 minutes. The upper plate is then lowered to 50 μm (instrument setting) above the desired test gap (1.5 mm). Excess material is trimmed away and the upper plate is lowered to the desired gap. Measurements are taken under a nitrogen purge with a flow rate of 5 L / min. The default creep time is set for 2 hours. Each sample is compression molded into a "2 mm thick x 25 mm diameter" circular plaque at 177°C for 5 minutes under a pressure of 10 MPa in air. The sample is then removed from the press and placed on a counter to cool.
[0134] All of the samples were subjected to a constant low shear stress of 20 Pa to ensure that the steady state shear rate was low enough to be in the Newtonian region. The resulting steady state shear rate was 10 for the samples in this study. -3 ~10 -4 s -1 The steady state was determined by taking a linear regression of all the data in the last 10% time window of a plot of log(J(t)) versus log(t), where J(t) is the creep compliance and t is the creep time. If the slope of the linear regression is greater than 0.97, the steady state is considered to have been reached and the creep test is then stopped. In all cases in this test, the slope meets the criterion within 1 hour. The steady state shear rate is determined from the slope of the linear regression of all the data points in the last 10% time window of a plot of "ε versus t", where ε is strain. The creep zero shear viscosity is determined from the ratio of the applied stress to the steady state shear rate.
[0135] To determine if a sample has degraded during the creep test, small amplitude oscillatory shear tests are performed on the same sample from 0.1 to 100 rad / sec before and after the creep test. The complex viscosity values of the two tests are compared. If the difference in viscosity value at 0.1 rad / sec is greater than 5%, the sample is considered to have degraded during the creep test and the results are discarded.
[0136] Zero Shear Viscosity Ratio (ZSVR) Zero Shear Viscosity Ratio (ZSVR) is defined as the ratio of the zero shear viscosity (ZSV) of a branched polyethylene material to the ZSV of a linear polyethylene material at equivalent average molecular weight according to the following equation: ZSVR=η 0B / η 0L = η 0B / (2.29 -15 XMwt 3.65 ) ZSV values are obtained from creep tests at 190°C by the method described above. Mwt is determined using gel permeation chromatography as described above. A correlation between the ZSV of a linear polyethylene and its molecular weight was established based on a series of linear polyethylene reference samples. A lower ZSVR indicates a lower level of long chain branching.
[0137] 13 Branching measurements using C NMR Sample preparation Samples are prepared by adding approximately 2.7 g of a 50 / 50 mixture of tetrachloroethane-d2 / orthodichlorobenzene containing 0.025 M Cr(AcAc)3 to 0.20-0.30 g of sample in a Norell 1001-7 10 mm NMR tube. Oxygen is removed by purging the tube with N2 for 1 min. Samples are dissolved and homogenized by heating the tube and its contents to 120-140 °C using a heating block and vortex mixer. Each sample is visually inspected to ensure homogeneity. Thoroughly mixed samples are not allowed to cool prior to insertion into the heated NMR sample changer and / or NMR probe.
[0138] Data Acquisition Parameters Data are collected using a Bruker 600 MHz spectrometer equipped with a Bruker 10 mm multinuclear high temperature CryoProbe. Data are acquired at a sample temperature of 120°C using 1280 voltage transients per data file, a pulse repetition delay of 7.8 seconds, a flip angle of 90 degrees, and inverse gated decoupling. All measurements are performed with the sample non-spinning in locked mode. Samples are allowed to thermally equilibrate prior to data acquisition. 13 C NMR chemical shifts are internally referenced to the EEE triad at 30.0 ppm. Data are processed into spectra and appropriate peaks are integrated (to quantify branching) and then either using one or more peak integrals or averaging over total branches / 1000 C. If branching is not detected, the integrals and signal-to-noise ratios of peaks such as those due to chain ends are used to calculate the detection limit of the spectrum.
[0139] 1 Unsaturation measurement using H NMR Add the stock solution (3.26 g) to 0.10–0.13 g of polymer sample in a 10 mm NMR tube. The stock solution is 0.001 M Cr 3+ A mixture of tetrachloroethane-d2 (TCE) and perchloroethylene (50:50, w:w) with 0.001M Cr 3+ The solution in the tube is purged with N2 for 5 min to reduce the amount of oxygen. The sample is dissolved at 120-140 °C with periodic vortex mixing. 1 1 H NMR analysis is performed on a Bruker AVANCE 600 MHz spectrometer using a 10 mm cryoprobe at 120°C.
[0140] Two experiments are performed to measure the unsaturation, one control experiment and one double presaturation experiment. In the control experiment, the data are processed with an exponential window function with 0.7 Hz line broadening. 1 The signal from H is set to 100, and the integral value (I 合計) is used as the signal from the whole polymer in the control experiment. The total carbon number NC in the polymer is calculated by Equation 1A as follows: NC=I 合計 / 2 (Equation 1A).
[0141] For the double presaturation experiment, process the data with an exponential window function with 0.7 Hz line broadening and correct the baseline to approximately 7-4 ppm. 1 The signal from H is set to 100 and the corresponding integral for unsaturation (I ビニレン , I トリ置換 , I ビニル , and I ビニリデン ) was integrated. The use of NMR spectroscopy to determine polyethylenic unsaturation is known, see for example Busico, V., et al., Macromolecules, 2005, 38, 6988. The number of vinylene, trisubstituted, vinyl, and vinylidene unsaturated units is calculated as follows: N ビニレン =I ビニレン / 2 (Equation 2A), N トリ置換 =I トリ置換 (Equation 3A), N ビニル =I ビニル / 2 (Equation 4A), N ビニリデン =I ビニリデン / 2 (Equation 5A)
[0142] The unsaturated units per 1,000 total carbons, i.e., all polymer carbons including the backbone and branches, are calculated as follows: N ビニレン / 1,000C=(N ビニレン / NC)*1,000(Equation 6A), N 三置換 / 1,000C=(N 三置換 / NC)*1,000 (Equation 7A), N ビニル / 1,000C=(N ビニル / NCH2)*1,000 (Equation 8A), N ビニリデン / 1,000C=(N ビニリデン / NC)*1,000 (Equation 9A).
[0143] From the residual protons from TCE-d2 1 Set the chemical shift reference at 6.0 ppm for the H signal. A control is performed with a ZG pulse, NS=16, DS=2, AQ=1.82 s, D1=14 s (D1 is the relaxation delay). A double presaturation experiment is performed with a modified pulse sequence with O1P=1.354 ppm, O2P=0.960 ppm, NS=50, AQ=1.82 s, D1=1 s (D1 is the presaturation time), D13=13 s (D13 is the relaxation delay).
[0144] Some embodiments of the present invention will now be described in detail in the following examples. EXAMPLES
[0145] Polyethylene composition 1 The embodiments of the polyethylene-based compositions of the invention described in the examples below utilize Polyethylene Composition 1 and Polyethylene Composition 2. Polyethylene Composition 1 was prepared according to the following process and based on the reaction conditions reported in Table 1.
[0146] All raw materials (ethylene monomer) and process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) are purified with molecular sieves prior to introduction into the reaction environment. Hydrogen is supplied under pressure as a high purity grade and is not further purified. The reactor monomer feed stream is pressurized to above reaction pressure via a mechanical compressor. The solvent feed is pressurized to a pressure above reaction pressure with a pump. Individual catalyst components are batch diluted manually with purified solvent to specific component concentrations and pressurized to a pressure above reaction pressure. All reaction feed streams are metered with mass flow meters and independently controlled by computer automated valve control systems.
[0147] A continuous solution polymerization reactor consists of two liquid-filled, non-adiabatic, isothermal circulating loop reactors similar to a continuous stirred tank reactor (CSTR) with heat removal. Independent control of all unused solvent, monomer, hydrogen, and catalyst component feeds to each reactor is possible. The entire unused feed stream (solvent, monomer, and hydrogen) to each reactor is temperature controlled by passing the feed streams through heat exchangers. The entire unused feed to each polymerization reactor is injected into the reactor at two locations per reactor, with approximately equal reactor volumes between each injection location. The fresh feed to the first reactor is typically controlled such that each injector receives half of the total unused feed mass flow rate. The unused feed to the second reactor in series is typically controlled to maintain half of the total ethylene mass flow rate near each injector, and this injector typically has less than half of the total unused feed mass flow rate to the second reactor, since unreacted ethylene from the first reactor enters the second reactor adjacent to the low pressure unused feed.
[0148] The catalyst / cocatalyst components for each injector are injected into the polymerization reactor through specially designed injection stingers. Each catalyst / cocatalyst component is injected separately into the same relative position within the reactor with no contact time prior to the reactor. The main catalyst components are computer controlled to maintain individual reaction monomer conversions at specific targets. The cocatalyst components are fed based on a calculated, specified molar ratio to the main catalyst component.
[0149] The catalyst used in the first reactor is zirconium, [[2,2′′-[[bis[1-methylethyl)germylene]bis(methyleneoxy-κO)]bis[3′,5,5′-tris(1,1-dimethylethyl)-5′-octyl[1,1′:3′,1′-terphenyl]-2′-olato-κO]](2-)]dimethyl-, and has the chemical formula C 86 H 128 F2GeO4Zr and has the following structure ("Catalyst 1"): [ka] The catalyst used in the second reactor is zirconium, [[2,2''-[1,3-propanediylbis(oxy-κO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5'-(dimethyloctylsilyl)-3'-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-olato-κO]](2-)]dimethyl, and has the chemical formula C 107 H 154 N2O4Si2Zr and has the following structure ("Catalyst 2"): [ka]
[0150] Immediately after each reactor feed injection location, the feed stream is mixed with the contents of the circulation polymerization reactor using static mixing elements. The contents of each reactor are continuously circulated through a heat exchanger that serves to remove most of the heat of reaction and at a coolant side temperature that serves to maintain an isothermal reaction environment at the specified reaction temperature. Circulation around each reactor loop is provided by a pump.
[0151] The effluent from the first polymerization reactor (containing solvent, monomer, hydrogen, catalyst components, and molten polymer) exits the first reactor loop, passes through a control valve (responsible for maintaining the pressure of the first reactor at a specific target), and is injected into a second polymerization reactor of similar design. The final effluent from the second polymerization reactor enters a zone where the effluent is deactivated by addition and reaction with a suitable reagent (water). At this same reactor exit location, other additives are added for polymer stabilization. This final effluent stream passes through another set of static mixing elements to facilitate catalyst deactivation and additive dispersion.
[0152] Following catalyst deactivation and additive addition, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The isolated polymer melt is pelletized and collected. The non-polymer stream passes through various equipment that separates most of the ethylene removed from the system. Most of the solvent is recycled to the reactor after passing through a purification system. A small amount of solvent is purged from the process. Polyethylene Composition 1 was stabilized with a small amount (ppm) of stabilizer.
[0153] The polymerization conditions for polyethylene composition 1 are reported in Table 1. As seen in Table 1, cocatalyst 1 (bis(hydrogenated tallow alkyl)methyl, tetrakis(pentafluorophenyl)borate(1-)amine) and cocatalyst 2 (modified methylaluminoxane (MMAO)) are used as cocatalysts for catalyst 1 and catalyst 2, respectively.
[0154] Polyethylene composition 2 is prepared using the same process as polyethylene composition 1, using the same catalyst system and under comparable reaction conditions.
[0155] Additional properties of polyethylene composition 1 and polyethylene composition 2 were measured using the test methods described above and are reported in Table 2. The first polyethylene fraction refers to the polyethylene component from the first reactor and the second polyethylene fraction refers to the polyethylene fraction from the second reactor. [Table 1] [Table 2] *The detection limit for this assay was <3. **the goal
[0156] The densities of the first polyethylene fraction of polyethylene composition 1, the overall polyethylene composition 1, and the overall polyethylene composition 2 are measured as described above in the Test Methods section. The density of the first polyethylene fraction of polyethylene composition 2 is the target value. The density of the second polyethylene fraction is calculated using the following blending rules:
number
[0157] Polyethylene Composition 1 and Polyethylene Composition 2 are evaluated against two comparative resins. Comparative Composition A is ELITE™ 5960G, a high density reinforced polyethylene resin available from The Dow Chemical Company, without Hyperform HPN-20E. Comparative Composition A has a viscosity of 0.962 g / cm 3 and a melt index (I2) of 0.85 g / 10 min. 3 and a melt index (I2) of 1.2 g / 10 min, and contains approximately 1200 ppm of Hyperform HPN-20E. Table 3 shows some of the differences in the polymer design of these resins. [Table 3]
[0158] Example 1 Polyethylene composition 1 and comparative compositions A and B are evaluated on a blown film line. The resins are dry blended with Hyperform HPN-20E nucleating agent (Milliken Chemical) provided in a masterbatch to target different final loadings of HPN-20E nucleating agent ("HPN-20E") (targets: 0, 250, 750, 1250, 2500, and 5000 ppm HPN-20E loading) and further evaluate water vapor barrier properties (MVTR or WVTR). The HPN-20E masterbatch contains 3 weight percent HPN-20E, 1.5 weight percent silica, 0.5 weight percent hydrotalcite, 5 weight percent antioxidant, and 90 weight percent carrier resin. The carrier resin has a viscosity of 0.965 g / cm. 3and a melt index (I2) of 8.0 g / 10 min. Hyperform HPN-20E is a narrow molecular weight distribution high density polyethylene homopolymer having a density of 8.0 g / 10 min and a melt index (I2) of 8.0 g / 10 min. Hyperform HPN-20E contains about 66 weight percent calcium salt of 1,2-cyclohexanedicarboxylic acid and about 34 weight percent zinc stearate / palmitate.
[0159] The blown film line utilizes a twin screw extruder where the specific resins and nucleating agents are dry blended and then fed into a 2 inch diameter extrusion ring at a nominal rate of 15 lbs / hr. The extruder die temperature is set at 215-235°C. The blown film structure is a monolayer film with a target thickness of 2 mils. The blow up ratio was targeted at 2.5, the frost line height ranged from approximately 9-11 inches, and the lay flat was approximately 7.9 inches. Approximately 100 feet of bubble film is produced and then split into two films.
[0160] The water vapor transmission rate (WVTR) of the film was measured and was calculated to be 0.10 (g-mil) / (100 in 2 A WVTR of (g-mils) / (100 in. days) is particularly desirable. 2 The results are shown in Table 4 in units of days. [Table 4]
[0161] In particular, compositions that are blends of 250-1250 ppm of Polyethylene Composition 1 with HPN-20E represent polyethylene-based compositions according to some embodiments of the present invention. Compositions that are blends with Comparative Composition A or Comparative Composition B are comparative examples. Note that data for Comparative Composition B is not available at 0-750 ppm since HPN-20E is commercially available at approximately 1200 ppm. The polyethylene-based composition of the present invention using HPN-20E at 250 ppm provides the best WVTR performance.
[0162] Example 2 Additional film samples are made using a Dr. Collin 3-layer coextrusion blown film line. Instead of the twin screw extruder used in Example 1, this blown film line has a single screw extruder feeding a 2.36 inch diameter extrusion ring. The nominal run rate is 30 pounds / hour and the extruder die temperature is set at about 215°C. The blown film structure is a monolayer film with a target thickness of 2 mils. The blow-up ratio was targeted at 2.5, the frost line height was about 5.5 inches, and the lay flat was about 10 inches. Approximately 100 feet of bubble film is produced and split into two films.
[0163] Three polyethylene-based compositions are made with polyethylene composition 1 by: (1) dry blending polyethylene composition 1 with HPN-20E masterbatch (described in Example 1) in a single screw extruder in a blown film line ("dry blend"); (2) melt blending polyethylene composition 1 with HPN-20E in a ZSK-26 extruder and then feeding the blended composition to a blown film line ("melt blend"); and (3) melt blending polyethylene composition 1 with HPN-20E masterbatch (described in Example 1) in a ZSK-26 extruder, followed by reprocessing the blended composition again in a ZSL-26 extruder and then feeding the blend to a blown film line ("melt blend x 2"). The results are shown in Table 5. [Table 5]
[0164] Each of the above compositions utilizing 250-750 ppm HPN-20E represents a polyethylene-based composition according to some embodiments of the present invention. In particular, melt blends of polyethylene composition 1 with 250HPN-20E provided particularly desirable WVTR values that were nearly 20% lower than comparative composition B.
[0165] Example 3 In this example, several multilayer films are made using a seven-layer Alpine blown film line. The multilayer films are made with five different layers, having a total nominal thickness of 2.2 mils and formed with a blow-up ratio of 2.5. The film structure is Layer A (15%) / Layer B (20%) / Layer C (30%) / Layer D (20%) / Layer E (15%). Layer A is formed from ELITE™ 5960G1 (The Dow Chemical Company). Layers B and D are each formed from INNATE™ TH60 (The Dow Chemical Company). Layer E is a sealant layer and is formed from SEALUTION™ 220 (The Dow Chemical Company). Layer C is a barrier layer and is detailed in Table 6 below. A blend of polyethylene composition 1 and masterbatch HPN-20E (described in Example 1) is either dry blended in an extruder feeding an Alpine blown film line ("dry blend") or melt blended in a ZSK40 twin screw extruder and then provided to an extruder feeding an Alpine blown film line ("melt blend"). Comparative composition B is evaluated in layer C as commercially available. The WVTR of the samples was measured and the results are shown in Table 6. [Table 6]
[0166] Blends of polyethylene composition 1 with 250-750 ppm HPN-20E represent polyethylene-based compositions according to some embodiments of the present invention. Providing a polyethylene-based composition with 750 ppm HPN-20E provides particularly desirable WVTR results. In particular, melt blends of polyethylene composition 1 with 750 ppm HPN-20E provide an improvement in WVTR of about 15% compared to comparative composition B.
[0167] Example 4 In this example, the dusting of films formed from Polyethylene Composition 2 and Comparative Resin B is compared.
[0168] Polyethylene composition 2 is melt blended with Hyperform HPN-20E nucleating agent (Milliken Chemical) provided in Starbatch ("HPN-20E") along with masterbatch silica, hydrotalcite, antioxidant, and HDPE carrier resin. The masterbatch contains 3 weight percent HPN-20E, 1.5 weight percent silica, 0.5 weight percent hydrotalcite, 5 weight percent antioxidant, and 90 weight percent carrier resin. The carrier resin has a viscosity of 0.965 g / cm. 3 and a melt index (I2) of 8.0 g / 10 min. Hyperform HPN-20E comprises about 66 weight percent calcium salt of 1,2-cyclohexanedicarboxylic acid and about 34 weight percent zinc stearate / palmitate. The polyethylene-based composition of the present invention formed from Polyethylene Composition 2 and the masterbatch ("Polyethylene-Based Composition 2") comprises 750 ppm HPN-20E, 375 ppm silica, 125 ppm hydrotalcite, and 1,250 ppm antioxidant, based on the total weight of the polyethylene-based composition.
[0169] Comparative composition B contains about 1200 ppm HPN-20E and is believed to be free of silica.
[0170] Monolayer films with a target thickness of 2 mils are produced from polyethylene-based composition 2 and comparative composition B on a blown film line. The blown film line is equipped with a single screw extruder using an 8-inch DSB II screw design, capable of an output rate of polyethylene approaching 600 lbs / hr. The target temperature profile during extrusion is 177°C, 218°C, 193°C, 163°C, 163°C, 221°C, and 227°C through barrels 1-5, the screen block, and the lower and upper dies, respectively. To produce the film, the composition is delivered to an 8-inch blown film die with a die gap of 70 mils and an output rate of 10.4 lbs / hr / inch of die circumference. The target melt temperature is 227°C, and the blow-up ratio is maintained at 2.5 to 1. The air temperature of the air ring and air cooling unit is 7.2°C. The frost line height averages 34 inches. Film thickness is controlled to within ±10% at 2 mils by adjusting the nip roller speed. The bubble layflat is 31 inches wide. The film is wound onto a roll before being slit.
[0171] The films are evaluated for dusting. Dust from the films is collected on an 8.5" x 11" black felt sheet adhered to the stationary roller of the slitter / rewinder. The film slid over the stationary felt sheet as it was wound on the machine. Dust is collected from 800 feet of each sample at a run speed of 200 feet / minute. The black felt samples are then carefully removed and visually inspected. The film samples formed from polyethylene-based composition 2 showed less dusting than the film samples formed from comparative composition B.
Claims
1. 1. A polyethylene-based composition suitable for packaging applications, comprising: (a) at least 97 wt.% of a polyethylene composition, based on the total weight of the polyethylene composition, (i) 0.935-0.947g / cm 3 and a melt index (I) of less than 0.1 g / 10 min. 2 25 to 37 weight percent of a first polyethylene fraction having a copolymer having a carboxylic acid group; (ii) 63 to 75 weight percent of a second polyethylene fraction; and (b) 90 to 540 ppm, based on the total weight of the polyethylene-based composition, of a calcium salt of 1,2-cyclohexanedicarboxylic acid; The polyethylene composition comprises: 13 and having less than 0.10 branches per 1,000 carbon atoms as measured using C NMR, and the polyethylene composition has a density of at least 0.965 g / cm 3 and the melt index (I 2 ) is 0.5 to 10 g / 10 min.
2. The polyethylene composition has a viscosity of 0.940 to 0.947 g / cm 3 25 to 37 weight percent of the first polyethylene fraction having a density in the range of 0.970 g / cm 3 and 63 to 75 weight percent of the second polyethylene fraction having a density of at least 100% by mass.
3. The melt index (I 2 3. The polyethylene-based composition according to claim 1 or claim 2, wherein the elongation constant (Ef) is 2.5 g / 10 min or less.
4. The melt index (I 2 ) versus the melt index (I 2 4. The polyethylene-based composition according to claim 1, wherein the ratio of
5. The polyethylene-based composition according to any one of claims 1 to 4, wherein the polyethylene-based composition has a zero shear viscosity ratio of less than 2.
0.
6. The polyethylene-based composition of any one of claims 1 to 5, further comprising a fatty acid metal salt in an amount of 45 to 360 ppm, based on the total weight of the composition.
7. The polyethylene-based composition of any one of claims 1 to 6, further comprising silica in an amount of 75 to 800 ppm, based on the total weight of the composition.
8. The polyethylene-based composition of any one of claims 1 to 7, wherein the polyethylene composition has less than 25 non-vinyl unsaturations per million carbons.
9. A film comprising the polyethylene composition according to any one of claims 1 to 8.
10. An article comprising the polyethylene-based composition of any one of claims 1 to 8.
Citation Information
Patent Citations
Barrier film for food packaging
JP2010510333A
Ethylene-based polymers and their use
JP2012532231A
Catalyst system for olefin polymerization
JP2016503103A
Hot-fill process using closures made from bimodal polyethylene compositions
JP2019501251A
Nucleated polyethylene blends and their use in molded articles
JP2019529649A
